Vocabulary as a possible index of language development among students of Zamboanga City High School, Zamboanga City - Dumaran, Cristeta Madrigal 1939- (1969)
Thesis (M.A. Language Education)--University of the Philippines, Diliman.
Vita.
Keywords: Language arts (Secondary) -- Philippines -- Zamboanga City (Zamboanga del Sur).; English language -- Glossaries, vocabularies, etc; English language -- Composition and exercises -- Study and teaching (Secondary) -- Philippines -- Zamboanga City (Zamboanga del Sur) -- Evaluation; Vocabulary